ORIGINAL PAPER Fractional flow reserve measurement in patients with multivessel coronary artery disease and borderline lesions prevents unnecessary revascularization procedures: results of the 3.5-year follow-up - Reczuch, Krzysztof; Jankowska, Ewa; Szajn, Grzegorz; Telichowski, Artur; Porada, Adam; Banasiak, Waldemar; Ponikowski, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2005)
Background: Patients with multivessel coronary artery disease (CAD) are treated either with complex percutaneous coronary interventions (PCI) or coronary artery bypass grafting. There is no evidence that ad hoc PCI of another intermediate lesion is beneficial for the patient. However, postponing PCI until noninvasive functional tests have been performed is not a widespread strategy for many reasons. In 2004 we presented 15-month follow-up results of a cohort of patients with multivessel CAD, borderline lesions, and left anterior descending artery (LAD) involvement who were treated with PCI only when functional significance of the lesions was confirmed with measurement of fractional flow reserve (FFR). Aim of the present study was to present 3.5-year follow-up results of the cohort. Methods: The study group consisted of 16 patients with stable angina (11 males, mean age of 60±9 years) with 34 borderline lesions localised in the main epicardial coronary arteries. Each lesion was subject to FFR measurement. \"Ad hoc\" PCI was performed when FFR was 0.75. Results: Of 34 lesions, in 8 lesions (23%) FFR value was 0.75 and these lesions were treated conservatively. Duration of follow-up ranged from 33 to 56 months (x±SD – 43±6 months, median – 43 months). Four major adverse coronary events and revascularization procedures occurred and can be attributed to 3 lesions (9%). However, only 2 events can be attributed to lesions treated conservatively (6%). Conclusions: 1. In patients with multivessel CAD and borderline lesions measurement of FFR makes it possible to identify significant stenoses the dilatation of which results in disappearance of angina without performing complex angioplasty. 2. Deferral of PCI in functionally insignificant lesions is associated with good clinical outcomes in 3.5-year follow-up.